2020
DOI: 10.3390/pathogens9090741
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Infectious Agent of Translucent Post-Larva Disease (TPD) in Penaeus vannamei

Abstract: A new emerging disease called “translucent post-larvae disease” (TPD) or “glass post-larvae disease” (GPD) of Penaeus vannamei, characterized by pale or colorless hepatopancreas and digestive tract, has become an urgent threat to the shrimp farming industry. Following this clue that treatment of an antibacterial agent could alleviate the disease, systematic investigation of the potential infectious agent of TPD was conducted using bacterial identification and artificial challenge tests to fulfill Koch’s postul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Its pathogenicity is usually determined by the interaction between the bacterium and the host cell. The prediction of virulence genes and the genetic analyses of bacterial virulence factors showed that pathogens are distinguished from their non‐pathogenic relatives by the presence of specific pathogenicity genes (Han, Tang, & Lightner 2015; Zou et al., 2020). In the normal PCR, virulence genes (pirA and pirB) of the isolated bacteria were confirmed existence.…”
Section: Discussionmentioning
confidence: 99%
“…Its pathogenicity is usually determined by the interaction between the bacterium and the host cell. The prediction of virulence genes and the genetic analyses of bacterial virulence factors showed that pathogens are distinguished from their non‐pathogenic relatives by the presence of specific pathogenicity genes (Han, Tang, & Lightner 2015; Zou et al., 2020). In the normal PCR, virulence genes (pirA and pirB) of the isolated bacteria were confirmed existence.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with Vibrio parahaemolyticus in the early stages of shrimp, particularly the Zoea stage, often results in huge death of larvae (Angthong et al, 2021). In China, an unique illness known as "translucent postlarvae disease" (TPD) or "glass post-larvae disease" (GPD) caused by highly pathogenic vibrios with virulence has lately caused significant economic losses (Zou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Among various kinds of pathogens, Vibrio is considered as one of the most important hazards for shrimp culturing (Flegel, 2012;Ina-Salwany et al, 2019;Thitamadee et al, 2016). Many Vibrio species have been reported to be virulent to shrimp, for example V. harveyi (Rungrassamee et al, 2016;Soto-Rodriguez et al, 2012), V. alginolyticus (Lee et al, 1996;Selvin & Lipton, 2003;Vandenberghe et al, 1999), V. parahaemolyticus (Ananda Raja et al, 2017;Jia et al, 2018;Tran et al, 2013;Zhang et al, 2012;Zou et al, 2020), V. campbellii (Dong et al, 2017;Soto-Rodríguez et al, 2006), V. rotiferianus (Zhang et al, 2014), V. cholerae (Joseph et al, 2015), V. nigripulchritudo (Goarant & Merien, 2006;Walling et al, 2010) and V. penaecida Maningas et al, 2008).…”
Section: Introductionmentioning
confidence: 99%